Perancangan Ulang Tata Letak Gudang Menggunakan Metode BLOCPLAN di PT INTAN PRIMA KALORINDO - Anjis Rahel Napitupulu; Yogi Sirodz Gaos (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
This study aims to redesign the layout of three warehouse areas at PT Intan Prima Kalorindo, namely the inner warehouse, upper warehouse, and outer warehouse, to improve the efficiency of material flow and space utilization. The Blocplan method was used as a systematic approach to layout planning based on activity proximity (Activity Relationship Chart). Data were collected through observation, interviews, and direct measurements on site. The redesign results showed a significant improvement in efficiency across all three warehouses, with the highest R-score values of 0.60 for the inner warehouse, 0.61 for the upper warehouse, and 1.00 for the outer warehouse. Implementation was carried out gradually, with several adjustments made to accommodate actual field conditions. This research demonstrates that the Blocplan method is effective in redesigning warehouse layouts to support smooth operational performance at PT Intan Prima Kalorindo.